2000
DOI: 10.1620/tjem.191.85
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carnosine on Rats under Experimental Brain Ischemia

Abstract: The effect of dietary carnosine on the behavioral and biochemical characteristics of rats under experimental ischemia was studied. Carnosine was shown to improve the animals orientation and learning in "Open Field" and "T-Maze" tests, and this effect was accompanied with an increase in glutamate binding to N-methyl-D-aspartate (NMDA) receptors in brain synaptosomes. Long-term brain ischemia induced by both sides' occlusion of common carotid arteries resulted in 55% mortality of experimental rats, and those who… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 27 publications
0
8
0
2
Order By: Relevance
“…Stvolinsky et al and Gallant et al reported decreased mortality after ischemic attack in rats treated with carnosine (from 55% to 17%), with most learning parameters maintained at pre-ischemic levels [20,21]. One of the underlying mechanism of ischemic attack is thought to be oxidative damage due to the generation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Stvolinsky et al and Gallant et al reported decreased mortality after ischemic attack in rats treated with carnosine (from 55% to 17%), with most learning parameters maintained at pre-ischemic levels [20,21]. One of the underlying mechanism of ischemic attack is thought to be oxidative damage due to the generation of free radicals.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence that carnosine may exert protective action against a number of conditions associated with ischaemia (see Stvolinsky and Dobrota, 2000 and Refs. therein;Gallant et al, 2000;Rajanikant et al, 2007;Tang et al, 2007;Yasuhara et al, 2008), including when added after the ischaemic episode (Dobrota et al, 2005;Tang et al, 2007;Rajanikant et al, 2007), and type-2 diabetes has been obtained mostly from the study of animal models and cell culture (Lee et al, 2005;Shi et al, 2009;Kamel et al, 2008;Tanida et al, 2004). Evidence supporting a role for carnosine in controlling diabetic kidney disease in humans has emerged from a study of carnosinase polymorphisms which suggest that lower levels of serum carnosinase activity decreases the incidence of kidney disease in type-2 diabetics (Ahluwalia et al, 2011;Janssen et al, 2005;Freedman et al, 2007;Sauerhoefer et al, 2005).…”
Section: Defence Against Mg By An Endogenous Agent Carnosinementioning
confidence: 99%
“…12,13 In focal ischemia, we have previously shown that intraperitoneally administrated carnosine reduced brain damage in mouse ischemia models induced by permanent middle cerebral artery occlusion (pMCAO). 14 We also showed that carnosine is the most effective among several carnosine analogues in reducing pMCAO-induced infarction volumes.…”
Section: Introductionmentioning
confidence: 99%